Methotrexate plus narrow band ultraviolet B (NBUVB) versus methotrexate alone in the treatment of moderate to severe plaque psoriasis: A randomized clinical trial - Khadka, Dhan Keshar; Agrawal, S; Dhali, T K (Nepal Journal of Dermatology, Venereology & Leprology, 2016)
Introduction: Psoriasis is a chronic, recurring inflammatory disease affecting the skin, joints and nails that has a significant negative impact on the quality of life. Efficacy of combination of methotrexate/narrowband ultraviolet B (NBUVB) phototherapy in the treatment of psoriasis has been rarely assessed. Objectives: To compare the therapeutic efficacy of methotrexate plus NBUVB phototherapy combination vs. methotrexate in the treatment of moderate to severe chronic plaque psoriasis. Material and methods: Seventy-nine patients with chronic plaque-type psoriasis (body surface area involvement >2%) were randomized to receive either methotrexate/NBUVB phototherapy (group A) or methotrexate (group B). End point of treatment was 75% reduction in Psoriasis Area and Severity Index (PASI75) Score or up to 12weeks, whichever was earlier. Patients were then followed up for a period of 12 weeks for assessment of adverse effect, DLQI and relapse. Results: Of 79 patients, 69 completed the treatment period and follow-up. PASI 75 was achieved in 35/39(89%) patients in group A and 34/40(85%) patients in group B (P=0.052). The mean number of weeks (P = 0.031), the mean cumulative dose of NBUVB (8.2±3.5J/cm2)) and the mean number of phototherapy sessions (12±3)) required to achieve PASI 75 were less in group A compared with group B. There was no significant difference in the number of patients who relapsed during the follow- up period (P = 0.68). Conclusion: Combination of methotrexate and NBUVB phototherapy provides more rapid clinical improvement compared with methotrexate monotherapy in the treatment for chronic plaque-type psoriasis. NJDVL Vol. 13, No. 1, 2015 Page: 12-23